Reflective Practice: its Contributions for Initial Pre-service Teachers and Further Teachers’ Professional Development - Muhamad Ahsanu (JPKMI (Jurnal Pengabdian Kepada Masyarakat Indonesia), 2021)
This article deals with the notion of reflective practice (RP) and how it may contribute to the professional development in teacher education programs especially for pre-service teachers and in-service teachers within the context of Indonesia. It aims to explore and explain the stance and features of RP and how it can serve to help both pre-service and in-service teachers improve their teaching quality and develop their teaching professionalism, especially those involved in English language teaching (ELT). This article examines the feasibility of this concept to be applied in Indonesian pedagogical contexts. Being widely accepted as an empowering teaching mode practice in most parts of the world, this RP plays a central role in triggering teachers' professional development, leading the teachers to be self-learning, autonomous learning, self-evaluating, and problem-solving-oriented practitioners. The research method used in this article is library research, through which the standpoint and characteristics of RP are explored and disclosed, and RP's potential can be maximized systematically. This library research method is realized based on the five research problems posed in this article. The same data on RP were extracted from research articles and textbooks on RP. The main findings suggest such aspects as the conceptualization of RP, defining features of RP practitioners, benefits teachers can gain from RP, and potential contributions of RP for both pre-service and in-service teachers' teaching competence and continual professional development. Hence, this RP article potentially provides a meaningful paradigm for language teachers and enriches their pedagogical repertoire.  Thus, this article brings about two important notes. First, it theoretically portrays how RP can meaningfully affect the efficacy of ELT practice in Indonesia. Secondly, it fundamentally sets out RP conceptualization as the basis for professional teaching practice through continuous learning and development. That is, learning to develop through a critical self-evaluation of teachers' teaching practice